Space-based optical observation system suitable for micro satellite - Piattoni, Jacopo <1986> (Alma Mater Studiorum - Università di Bologna, 2015)
The PhD research activity has taken place in the space debris field. In detail, it is focused on the possibility of detecting space debris from the space based platform. The research is focused at the same time on the software and the hardware of this detection system. For the software, a program has been developed for being able to detect an object in space and locate it in the sky solving the star field. For the hardware, the possibility of adapting a ground telescope for space activity has been considered and it has been tested on a possible electronic board.